Frequency of Attendance to Dental Consultation in High School Students from Pereira, and the Associated Emotional Factors (Revista Nacional de Odontología, 2015)
Introduction: This study aims to identify the frequency of dental consultation and the emotional factors associated in students of ninth year of Hans Drews Arango High School in the Municipality of Pereira, in 2014.Materials and Methods: study with application of two of surveys in 20 students. A mixed-approach descriptive study was performed. The quantitative component takes elements from a cross sectional study and data was gathered in the qualitative section by the application of pedagogical workshops with the use of field diaries. The analysis of the quantitative data was made on tabulation and analysis of the variables in the program Windows Excel 2010. The qualitative analysis was based on the information in the field diaries, and a process of identification of meaning units, codification and categorization was carried out.Results: 30% of the interviewees reported not to attend dental consultations, 20% to 25% of the people not attending dental consultation argue economic reasons and distance from the dental practice. Likewise, fear was the most relevant feeling among the students, especially towards needles, expressed by visual and oral expressions. They also expressed feelings associated with fear, anxiety and muscular tension.Discussion: These results revealed that fear and anxiety may be the motional factors that influenced attendance to dental consultation.
Keywords: anxiety to dental treatment; dental practices; oral health